High-magnification Faraday rotation imaging and analysis of X-pinch implosion dynamics - Dowhan,GV; Shah,AP; Sporer,BJ; Jordan,NM; Bland,SN; Lebedev,SV; Smith,RA; Suttle,L; Pikuz,SA; Mcbride,RD (Review of Scientific Instruments, 2024)
An X-pinch load driven by an intense current pulse (>100 kA in ∼100 ns) can result in the formation of a small radius, runaway compressional micro-pinch. A micro-pinch is characterized by a hot (>1 keV), current-driven (>100 kA), high-density plasma column (near solid density) with a small neck diameter (1–10 μm), a short axial extent (<1 mm), and a short duration (.1 ns). With material pressures often well into the multi-Mbar regime, a micro-pinch plasma often radiates an intense, sub-ns burst of sub-keV to multi-keV x-rays. A low-density coronal plasma immediately surrounding the dense plasma neck could potentially shunt current away from the neck and thus reduce the magnetic drive pressure applied to the neck. To study the current distribution in the coronal plasma, a Faraday rotation imaging diagnostic (1064 nm) capable of producing simultaneous high-magnification polarimetric and interferometric images has been developed for the MAIZE facility at the University of Michigan. Designed with a variable magnification (1–10×), this diagnostic achieves a spatialresolution of approximately 35 μm, which is useful for resolving the ∼100-μm-scale coronal plasma immediately surrounding the dense core. This system has now been used on a reduced-output MAIZE (100–200 kA, 150 ns) to assess the radial distribution of drive current immediately surrounding the dense micro-pinch neck. The total current enclosed was found to increase as a function of radius, r, from a value of ≈ 50 ± 25 kA at r ≈ 140 μm (at the edge of the dense neck) to a maximal value of ≈ 150 ± 75 kA for r ≥ 225 μm. This corresponds to a peak magnetic drive pressure of ≈ 75 ± 50 kbar at r ≈ 225 μm. The limitations of these measurements are discussed in the paper.